1990
DOI: 10.1289/ehp.9088129
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of thioguanine-resistant lymphocytes from mice irradiated in vivo.

Abstract: Adult mice were Co-60 gamma irradiated, and 7 months later splenocytes were isolated, cultured in microwells, and the frequency of hprt-deficient mutants was determined by measuring the cloning efficiency in media with 6-thioguanine. The mutant frequency at 2, 4, and 6 Gy was 1.6 x 10(-5), 4.4 x 10(-5), and 12.7 x 10(-5), respectively. The frequency of spontaneous mutants was 2.5 x 10(-6). The effect of metabolic cooperation on the cloning efficiency of thioguanine-resistant T-cells in selective medium was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Irradiation (6,19), and to a lesser extent, alkylating agents (9,10), have been shown to increase FMC. Azathioprine also can induce somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation (6,19), and to a lesser extent, alkylating agents (9,10), have been shown to increase FMC. Azathioprine also can induce somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of dosedependent radiation mutagenesis in mice has been demonstrated in a number of studies [Dempsey and Morley 1986;Lorenz et al, 1990Lorenz et al, , 1993Lorenz et al, , 1994Grdina et al, 1992;Kataoka et al, 1992Kataoka et al, , 1993Gaziev et al, 1995;Klarmann et al, 1995;Dobrovolsky et al, 2002;Liang et al, 2007]. However, the more extensive evaluation of time elapsed after acute g irradiation revealed that mutant frequency dependence on dose shifted between 3 and 5 weeks and 10-53 weeks, from being clearly quadratic at the peak of mutant recovery in weeks 3-5 to a statistically strong but less-defined dose relationship in the later time frame.…”
Section: Discussionmentioning
confidence: 99%